Working Paper No. 63, On Karl Polanyi and His Conception of Fascism - Mistkawi, Serene (Working Papers in Economics, 2022)
This inquiry seeks to establish that the writings of author Karl Polanyi offered insights into key variables and historical conditions that gave rise to the system we know of as “fascism.” Integral to his insights, Polanyi describes economic conditions attendant for fascism to emerge, with one condition noted as widespread and persistent unemployment. Polanyi stresses that fascism needs to be understood as reactionary, a responding to features integral to classical liberalism. Considering a broad historical context Polanyi teaches us of the political conditions necessary for fascism to emerge and take form as political movements wielding power. He considers conflicts in aims between economic and political institutions. In addition, Polanyi analyzes some implications of a changing market, as well as some effects that a changing market might have over individual freedoms, as well as some of the complexities that can be associated with regulation.
Economics
Keywords: classical liberalism; currency; fascism; interventionism; regulation

The Rise of the Capital-State and Neo-Nationalism: A New Polanyian Moment - Svitych, Oleksandr (Brill, 2022)
Political Science
Keywords: critical social sciences; global studies; neo-nationalism; populism; social sciences; sociology & anthropology

Karl Polanyi and the Rise of Fascism - England, Christopher M. (New Political Science, 2022)
This article reconstructs Karl Polanyi’s account of fascism’s rise in his 1935 article, “The Essence of Fascism.” Following the elevation of Hitler to power in 1933, Polanyi embarked on a reassessment of Nietzsche, Othmar Spann, Spengler, Evola, and other figures of the interwar conservative revolution. He argues that the fascist quest for national unity emerges when 19th century liberalism fails to address the growing atomization and economic dislocation of modern society. On the one hand, fascism valorizes the mythopoetic, prehistorical vitalism that liberal rationalism and social democracy sought to purge from public life. On the other, fascism aspires to a higher form of elitist, technological mastery than egalitarian states can achieve. These tensions, he predicts, will result in the radicalization and collapse of fascist regimes in a European war. This article illuminates Polanyi’s deep understanding of political modernity and the contemporary implications of his philosophical critique of the far right.
Political Science
Keywords: Karl Polanyi; conservative revolution; fascism; modernity; radical right

Karl Polanyi’s ‘socialist accounting’ and ‘overview’ in the age of data analytics - Rief, Silvia (New Political Economy, 2022)
Digital capitalism’s information infrastructure is the subject of contentious debates concerning its transformative effects on the political economy and society. A frequent proposition, referring to older arguments of the ‘socialist calculation debate’, is that with big data analytics the pro-market arguments of neoliberal economists such as Hayek or Mises become obsolete. This article critically examines this proposition by drawing on Karl Polanyi’s notion of overview; a core theme in his outlines of a socialist economy and accounting written in the 1920s. In these contributions to the early Austrian socialist calculation debate, Polanyi discusses how to gain knowledge of the economic and social processes in such a way that the economy can be democratically governed according to its socialist aims and purposes. This article highlights the relevance of Polanyi’s work on socialist accounting, along with his later perspectives on technology and on social scientific method, for reflecting upon data- and algorithm-driven economic governance. Polanyi’s critical analysis of abstraction effected through methods of knowing suggests a sceptical stance vis-à-vis current versions of technological ‘solutionism’, which places its faith in data and algorithms as tools for economic and social, or socialist, planning.
Sociology; Economics
Keywords: Karl Polanyi; accounting; data analytics; digital socialism; economic theory; overview; socialist accounting; socialist calculation

Polanyi and the Peasant Question in China: State, Peasant, and Land Relations in China, 1949–Present - Chuang, Julia; Yasuda, John (Politics & Society, 2022)
This article applies Karl Polanyi’s concept of a double movement to the trajectory of rural state policies in China since 1949. It argues that Chinese socialism created a contradictory social contract that has fueled an ongoing struggle between state and peasantry over the surplus generated from rural land. This struggle has shaped a historical oscillation between state policies that facilitate extraction of agricultural surpluses and policies that introduce social protections in the form of household farming and revitalized collective ownership. Based on secondary sources, this article compares the arc of rural policies during the Mao era and in the transition to and during the current state capitalist period. Then, based on original interview-based and ethnographic fieldwork undertaken in rural Sichuan Province, it analyzes the current introduction of urban and agrarian capital into the rural economy, revealing dynamics of a current countermovement from state-led extraction to compromise.
Publisher: SAGE Publications Inc
Keywords: China; Polanyi; agrarian transition; land politics; peasant politics; state capitalism; urbanization

Planning laissez-faire: Supranational central banking and structural reforms - Braun, Benjamin; Carlo, Donato Di; Diessner, Sebastian (Zeitschrift für Politikwissenschaft, 2022)
The mandate of the European Central Bank (ECB) does not extend to labor market and social policies at the national level. Why, despite the reputational costs, did the ECB act as a staunch advocate of structural labor market reforms from 1999 through 2015? We discuss this question through the theoretical lens of Karl Polanyi’s The Great Transformation. Although Polanyi has been a key reference point for the debate on the social consequences of European economic and monetary integration, one of his key insights has received surprisingly little attention—that central banks have the power to mitigate the impact of international economic integration on domestic social protection. Polanyi regarded central banks—much like trade unions—as national-level institutions of non-market coordination, acting as a protective buffer against the functional pressures of the fixed-exchange-rate monetary regime that was the international gold standard. By contrast, the ECB, as a supranational central bank, embodies these functional pressures. This helps explain why, rather than protecting existing social structures against the logic of the fixed-exchange-rate monetary regime, the ECB has sought to protect the monetary regime by going out of its way to re-shape labor market institutions at the national level.
Sociology
Keywords: European Central Bank; Europäische Zentralbank; Karl Polanyi; monetary integration; social protection; sozialpolitik; structural reforms; strukturreformen; wirtschafts- und währungsunion

Polanyi and social economy - Isaac, Barry L. (A Handbook of Economic Anthropology, 2022)
Substantivism stemmed from the writings of Hungarian lawyer-turned-historian Karl Polanyi, who argued that capitalism is a historically unique kind of economy that is disembedded from the social matrix. By implication, the socially embedded pre-capitalist economies studied by anthropologists, historians and classicists cannot be understood using the formal economics developed to analyze capitalist economies. Rather, new tools for analysing their 'substantive' economies must be employed. Substantivism was championed in economic anthropology by economist-turned-anthropologist George Dalton and became the reigning paradigm in the subfield during the 1960s. Formalism arose in opposition, arguing that capitalist and pre-capitalist economies differ in degree, not in kind, and thus can all be analysed using the tools of microeconomics. Formalism largely displaced substantivism during the 1970s and 1980s as anthropologists increasingly focused on the economic integration of the world's peasant sectors into their national and regional economies.
Economics; Anthropology

The Political Economy of Revolution: Karl Polanyi in Tahrir Square - Zayed, Hany (Theory, Culture & Society, 2022)
The causes and consequences of revolutionary change have long been the subject of scholarly debate. Through a systematic integration of political economic elements into an analysis of contemporary social transformations, this article joins this conversation by asking how Karl Polanyi’s double movement framework can clarify, and be extended by, the Egyptian Revolution of 2011. By embedding a nuanced account of neoliberalism in Egypt’s modern politics and by bringing those in dialogue with Polanyi’s theoretical apparatus, this article contends that there is a broad alignment between the first movement and the Egyptian neoliberal experience, a partial alignment between the second movement and the Egyptian Revolution, and a multilayered entanglement that implicates and encircles both movements. Not only does this research demonstrate that contemporary Egyptian history can find new currency in and be further illuminated by Polanyi’s political economy, it also critiques, complicates, reconceptualizes and extends Polanyi’s theoretical framework. In so doing, it redresses the underfocus of Polanyian political economy on the theory of revolution in general and the Egyptian Revolution in particular, problematizes extant accounts on neoliberalism and the double movement, and extends analyses between neoliberalism and revolution in political economy literatures. By clarifying our understanding of contemporary social change, this essay underscores how Polanyi’s work remains a pertinent, viable and valuable prism to examine momentous social transformations.
Publisher: SAGE Publications Ltd
Keywords: Egypt; Karl Polanyi; double movement; neoliberalism; revolution

Karl Polanyi and the Paradoxes of the Double Movement - Vail, John (Routledge, 2022)
This book offers a critical reconstruction of the double movement, the central thesis of Karl Polanyi’s The Great Transformation, one of the most influential books of the 20th century. The double movement is the establishment of a free market economy and the subsequent effort by society to ameliorate the destructive effects of the market. In Polanyi’s bold vision, the double movement constituted the hidden gear of social change and historical transformation within capitalism. The book is a forensic examination and critique of Polanyi’s argument. It develops an interpretive framework of the double movement as four interrelated social processes: the establishment of the self-regulating market, the rise of a market society that deepens and extends market imperatives, a social protection phase that constrains the market and safeguards society, and the contradictions and crises that result from this clash of social principles. The book will be an indispensable guide for students and scholars across the social sciences which illuminates the relevance of Polanyi’s insights to a critical understanding of the contemporary era –the scourge of insecurity and inequality, the multiple crises of neoliberalism, the rise of right wing populism- as well as those interested in egalitarian and emancipatory alternatives to capitalism.
Keywords: double movement; market society

Creativity, Pluralism, and Fictitious Narratives: Understanding IP Law Through Karl Polanyi - Suthersanen, Uma (2022)
For over a century, jurists have debated as to whether IP rights should be extended to this or that output such as photographs, computer programs, products of data aggregation, virtual objects, natural and organic materials, “creative” algorithms, and genes. What is surprising is the continuing and bifurcating discourse landscape: “IP law protects and rewards creativity” versus “IP law protects investment”. This paper suggests that IP law indiscriminately and simultaneously protected all sorts of res emanating from creative and entrepreneurial labour as well as from capital investment. Continued attempts to discuss or adjudicate IP law, policy and reform through strict conceptual silos such as creativity, labour, and investment are doomed narratives.Instead, I invite readers to appreciate that early modern rules in sensu lato were about mixed motivations of reward, investment, recognition, competition, honour, public interest, and more. The implicit suggestion in this paper is that the root cause of continuing legal conundrums today is the failure to appreciate the pattern set out by two related socio-legal mappings: (i) motivations for early rules in relation to creative and entrepreneurial labour and products in Europe; and (ii) the extent to which current IP norms and laws evolved to absorb such myriad motivations over five hundred years. I employ Karl Polanyi’s theory on the commodification of labour, including investment-backed labour, into tradeable, fictitious commodities, where law and property are recognised as vital institutional tools which disembed and re-embed society from/into the economy. Polanyi’s motivation ethos is effective in synthesising the different mapping points to create a pointilliste landscape which, in turn, shows why IP law only makes juridical sense if it is viewed as a pluralistic concept.
Law
Keywords: creativity; intellectual property; pluralism

The political trilemma of contemporary social-ecological transformation – lessons from Karl Polanyi’s The Great Transformation - Novy, Andreas (Globalizations, 2022)
This article advances Rodrik's political trilemma of the world economy by using insights from Polanyi’s The Great Transformation, which helps to grasp the interwoven dynamics of long-term transformations due to climate change and geopolitical reordering on one hand, and on the other short-term political ruptures due to countermovements. Rodrik's globalization trilemma shows the incompatibility of hyperglobalization with the need for an enlarged democratic policy space. Its nodes (globalization, nation state and democracy), however, have to be redefined to grasp contemporary dynamics of deglobalization. Based on a modified political trilemma of contemporary social-ecological transformation, I discuss and compare three visions and the resultant strategies: (1) Liberal globalism, focusing on hyperglobalization and individualism, (2) nationalistic capitalism, stressing national sovereignty and authoritarian governance, and (3) foundational economy based on planetary coexistence which combines selective economic deglobalization with a strengthening of a place-based foundational economy, and their respective social-ecological infrastructural configurations.
Political Science; Economics
Keywords: Great Transformation; The (Book); Polanyi; deglobalization; foundational economy; hyperglobalization; social-ecological transformation

Polanyi, Market Fundamentalism, and the Institutional Structure of Capitalism - Burlamaqui, Leonardo (CEBRI Brazilian Center for International Relations, 2022)
The basic proposition of this paper is that the so-called "new economic sociology", which is rooted in key ideas of Karl Polanyi, is an indispensable "tool" for two tasks: a) it provides us with a powerful critique of market fundamentalism, and b) it allows us to analyze the economic performance of contemporary capitalism by accessing the working of its institutional structure. From an analytical perspective, the paper suggests that Polanyian Economic Sociology is an essential complement to both the Schumpeterian and the Post-Keynesian perspectives in economics. This is especially so when it comes to the discussion of "socioeconomic stability" and, more precisely, as Keynes himself stated in the General Theory: to explain why capitalist economies manifest themselves in different ways and degrees, in spite of encompassing inherent elements of instability and unpredictability.The basic proposition of this paper is that the so-called "new economic sociology", which is rooted in key ideas of Karl Polanyi, is an indispensable "tool" for two tasks: a) it provides us with a powerful critique of market fundamentalism, and b) it allows us to analyze the economic performance of contemporary capitalism by accessing the working of its institutional structure. From an analytical perspective, the paper suggests that Polanyian Economic Sociology is an essential complement to both the Schumpeterian and the Post-Keynesian perspectives in economics. This is especially so when it comes to the discussion of "socioeconomic stability" and, more precisely, as Keynes himself stated in the General Theory: to explain why capitalist economies manifest themselves in different ways and degrees, in spite of encompassing inherent elements of instability and unpredictability.
International Relations
Keywords: Brazil; new economic sociology; political economy

Capitalism and Crisis: Thinking Through Capitalist Crisis with Schumpeter and Polanyi - Delanty, Gerard (Capitalism, Democracy, Socialism: Critical Debates, 2022)
The chapter offers an analysis of capitalist crisis through a reading and discussion of two seminal texts on capitalism, Joseph Schumpeter’s Capitalism, Socialism and Democracy [1943] and Karl Polanyi’s The Great Transformation [1944]. These inspiring works on economic history and social theory offer profound insights into the nature of capitalist crisis. Although written in the mid-twentieth century many of the insights in these books are of relevance to the current situation as capitalism undergoes another revulsion. While the two authors were very different – Polanyi a left-wing critic of capitalism; Schumpeter a politically right-wing economist who favoured capitalism – both were influenced by Marx’s analysis of capitalism and have helped to shape the debate on the crisis of capitalism. Indeed, Schumpeter was convinced Marx was mostly right in his prediction of the end of capitalism and the triumph of socialism. The chapter begins with a brief account of the Marxist theory capitalism in order to contextualise the discussion of the two theorists.
Political Science; Philosophy
Keywords: MARX; Karl; 1818-1883; Polanyi; SCHUMPETER; Joseph Alois; 1883-1950; capitalism; crisis